An Upstanding Goddess and Mother: Preliminary Thoughts on a Peculiar Depiction of Isis with Harpocrates on some Coins for Julia Domna - Schrauder, Julienne N. (PhDAI. Reports of the Young Research Network, 2024)
The article explores an unusual depiction of the Egyptian goddess Isis with her son Horus on a small group of coins minted for the Roman Empress Julia Domna, the wife of Emperor Septimius Severus. As a basis for the discussion of coins, the database Online Coins of the Roman Empire (OCRE) was used.